Sistem Penunjang Keputusan Penerapan Metode Topsis Pada Peningkatan Kinerja Karyawan - Alfaudzan, Adriansyah Muhamad; Gustian, Dudih (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
In determining the success of the company's work is influenced by human resource management (HR), one of the strategies in improving the quality of human resources work is to appreciate employee performance. The method used in determining this promotion is the topsis method, it is hoped that the assessment will be more precise because it is based on predetermined criteria and weights so that it will get more accurate results. For this reason, researchers try to help the problems mentioned above by developing a decision support system using the application of the TOPSIS method for this system. In this study we will know which employee performance is more accurate according to the company's determination, the results are in accordance with this study there are 5 candidates, 3 candidates who have high scores were selected, namely the first rank in the highest employee performance, the 1st is p1 with a preference value of 0.568796348, the second p2 with a preference value of 0.568579031, and the third rank p3 with the same preference value as p2.